PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN DAYA TARIK IKLAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK PT SIDO MUNCUL - Maria Guadalupe Kristi Wungu; Lukman Nul Hakim (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aims to determine the effect of product quality, brand image, and advertising attractiveness on the purchase decisions for PT Sido Muncul's products. The research method used is a quantitative method, with data collection through the distribution of questionnaires. The research population is consumers who have ever consumed products from PT Sido Muncul, out of which the sample was selected using a convenience sampling technique, which means that respondents were selected randomly, i.e. those whom the researcher accidentally encountered and selected with various considerations, including representativeness of the population and compliance with the requirements in the analysis tool. The collected data was then analyzed using multiple linear regression analysis techniques with the help of IBM Statistics software version SPSS 26